Mediating effect of smoking abstinence self-efficacy on association between health literacy and nicotine dependence of smokers in Qingdao, China - Yani Wang; Fei Qi; Jie Yang; Haiyan Xu; Aimiao Tian; Shasha Fang; Gongli Liu; Yaoqi Zhang; Shanpeng Li; Kunzheng Lv (PLoS ONE, 2026)
Objective Research on the mediating effect of smoking abstinence self-efficacy (SASE) on the relationship between health literacy and nicotine dependence is limited. This study examines the mechanisms through which health literacy influences addictive behavior and provides additional scientific evidence to inform smoking cessation interventions. Methods A total of 500 participants were recruited from 20 communities in Qingdao between June 2023 and June 2024. Spearman correlation analysis was used to explore relationships between nicotine dependence and other factors. Linear regression analyses were conducted to examine the relationships between health literacy, SASE, and nicotine dependence. Path analysis was performed using AMOS to assess the interactions among nicotine dependence, SASE, and health literacy, with mediation effects tested using the bootstrap method. Results After adjusting for potential confounders such as age, marital status, education level, and occupation, path analysis revealed a significant positive correlation between health literacy and SASE in habitual/addictive situations (SASEH; β = 0.185, p < 0.01). Nicotine dependence showed significant negative correlations with both health literacy (β = −0.289, p < 0.001) and SASEH (β = −0.513, p < 0.001). Bootstrap mediation tests confirmed that both the direct and indirect effects were statistically significant, with the mediating effect accounting for 24.7% of the total effect. Conclusions SASEH partially mediates the relationship between health literacy and nicotine dependence. Increasing health literacy not only directly reduces nicotine dependence but also improves SASE, which in turn further reduces dependence.